In vitro simulated gastrointestinal digestion and bioaccessibility of phenolic compounds and antioxidants of soursop (Annona muricata L.) peel and pulp - Domingues, Yasmin Ourives; Lemes, Geriel Araújo; de Oliveira, Fellipe Lopes [UNESP]; de Souza, Thamara Rosa; Silva, Bibiana; Bento, Juliana Aparecida Correia; Caldeira Morzelle, Maressa (Elsevier, 2024)
We evaluated the nutritional composition and quantified the bioactive compounds present in the soursop pulp and peel and investigated the impact of in vitro simulated gastrointestinal digestion on antioxidants and phenolic compounds of soursop. Soursop peel had a significant amount of fiber (17.6 g.100 g−1 w.b.), particularly insoluble fiber (16.8 g.100 g−1 w.b.), and higher levels of total phenolic compounds and antioxidant activity than pulp. The pulp has 30% higher levels of ascorbic acid than the peel (40.2 mg ascorbic acid 100 g−1). Gallic acid, benzoic acid, coumaric acid, ferulic acid, and hesperidin were detected in the peel and pulp of soursop. After in vitro simulated gastrointestinal digestion, results show that total phenolic compounds of the peel exhibited stability throughout the gastric and intestinal stages. In the pulp, simulated digestion showed an increase in total phenolic compounds on enteric II stage. About antioxidant compounds, peel showed stability in DPPH assay and higher accessibility in the enteric II stages (40% and 29%) on ABTS and FRAP assays. Soursop pulp increased accessibility in the gastric stage on DPPH and FRAP assay. In the ABTS assay, soursop pulp showed the highest values in enteric phase II. The in vitro accessibility of these compounds offers insights into their potential utilization by the organism. This knowledge holds significant implications for nutrition experts, as it can advise the development of healthier dietary habits.
Keywords: Antioxidants; Bioaccessibility; Bioactive compounds; By-products; Soursop